Mitigating the effect of linear infrastructure on arboreal mammals in dense forest: A canopy bridge trial. (12th January 2023) - Mitchell, Briony; Harrison, Lee; Ainley, Joanne; van der Ree, Rodney; Soanes, Kylie
Summary: Roads and other linear infrastructure create treeless gaps that can limit the movement of non‐flying, arboreal animals. These negative effects are particularly strong in dense forests, where even narrow infrastructure corridors represent a significant change in habitat structure. Artificial canopy bridges are an increasingly common approach to mitigating the barrier effect of roads and other linear infrastructure on the movement of arboreal mammals; however, questions remain about the success of various designs for different species. Here we conduct an experimental evaluation of the response of a critically endangered possum, Leadbeater's Possum ( Gymnobelideus leadbeateri ), to two artificial canopy bridge designs: single‐rope bridges and ladder bridges. We found that both bridges were used by Leadbeater's Possum and five other species of arboreal marsupial to cross narrow, forestry roads. However, Leadbeater's Possums crossed ladder bridges 13 times more often than the single‐rope design (average of 564.5 and 41.75 crossings per design respectively). Radiotelemetry conducted on four Leadbeater's Possums prior to bridge installation detected no road crossings, providing preliminary evidence that the bridges improved cross‐road movement. Ladder bridges appear to be the better design choice for a wider range of arboreal marsupials as they were used more frequently, offer greater stability, and provide better predator avoidance than single‐rope designs.